#TITLE_ALTERNATIVE# - IMAM GOZALI SUMANTRI (15112071), DIRGA
This Undergraduate Thesis discusses the height of sea surface from the observation and how it can be associated with a selected model of the global mean sea surface. To illustrate, the measurement of the actual sea surface is conducted by Global Navigation Satellite System observation by using Real-Time Precise Point Positioning method. Subsequently, tidal and non-tidal factors are taken out from the observed sea surface height to obtain the mean sea surface. Here, model of mean sea surface is generated from global geoid undulation and mean dynamic ocean topography. Eventually, the mean sea surface from the measurement is compared with the model of mean sea surface. It is found that the average of sea surfaces from the measurement and model are 21.61 and 21.51 meter respectively.